Campaña de publicidad social para el posicionamiento de la escuela municipal de ciegos 4 de enero en la ciudad de Guayaquil - Rodríguez Dumes, Cinthia Maricela (2017)
This research aims to create a Social Advertising campaign for the positioning of the Municipal School "4 de Enero" in the city of Guayaquil. In the course of the Municipal School of the blind "4 de Enero", it can be observed that the school in question has not developed a correct positioning of its image in the people who need the services of said school, because it lacks A correct communication and advertising strategy that motivates blind people and their families to know more about this school and its services……….